Catalytic routes towards acrylic acid, adipic acid and ε-caprolactam starting from biorenewables. Issue 3 (16th January 2015) - Beerthuis, Rolf; Rothenberg, Gadi; Shiju, N. Raveendran
Abstract : Go bio! We assess the biobased productions of three important bulk chemicals: acrylic acid, adipic acid and ε-caprolactam. These are the key monomers for high-end polymers and are all produced globally in excess of two million metric tons per year. Abstract : The majority of bulk chemicals are derived from crude oil, but the move to biorenewable resources is gaining both societal and commercial interest. Reviewing this transition, we first summarise the types of today's biomass sources and their economical relevance. Then, we assess the biobased productions of three important bulk chemicals: acrylic acid, adipic acid and ε-caprolactam. These are the key monomers for high-end polymers (polyacrylates, nylon 6.6 and nylon 6, respectively) and are all produced globally in excess of two million metric tons per year. The biobased routes for each target molecule are analysed separately, comparing the conventional processes with their sustainable alternatives. Some processes have already received extensive scientific attention. Other, more novel routes are also being considered. We find several common trends: For all three compounds, there are no commercial methods for direct conversion of biobased feedstocks. However, combinations of biotechnologically produced platform chemicals with subsequent chemical modifications are emerging and showing promising results. We then discuss several distinct strategies for implementing biorenewable processes. For each biotechnological and chemocatalytic route, current efficiencies and limitations are presented, but we urge that these routes should be assessed mainly on their potential and prospects for future application. Today, biorenewable routes cannot yet compete with their petrochemical equivalents. However, given that most of them are still in the early stages of development, we foresee their commercial implementation in the next two decades.